Uncovering Psychological Determinants and Coping Strategies in English Language Anxiety Among High School Students - Ameliana; Khoirul Huda; Buyun Khulel (Universitas Islam Tribakti Lirboyo Kediri, 2025)
English language proficiency is increasingly vital in today’s globalized world; however, many high school students experience English Learning Anxiety (ELA), which hinders their academic performance and language development. This study aims to explore the psychological determinants of English learning anxiety and to examine how students actively cope with anxiety in authentic classroom contexts. This research employed a qualitative descriptive design with thematic analysis, utilizing semi-structured interviews and classroom observations involving ten high school students from grades 10 and 11 at SMA Ahmad Yani 2 Baureno, Indonesia. The findings indicate that English learning anxiety is shaped by interrelated psychological determinants, including fear of negative evaluation, low self-confidence (self-efficacy), test anxiety, and learning motivation, rather than by isolated factors. Fear of negative evaluation and evaluative pressure emerged as particularly influential in constraining students’ classroom participation, while low self-confidence and test anxiety further intensified emotional distress. In response, students employed adaptive coping strategies, such as relaxation techniques, self-affirmation, peer support, and engagement in activity-based learning (e.g., storytelling, role-playing, and interactive tasks), to regulate anxiety during English learning. This study contributes novel, context-sensitive insights by foregrounding students’ lived experiences and coping processes, thereby extending existing ELA research beyond variable-centered explanations toward a dynamic, process-oriented understanding of anxiety regulation in secondary education contexts. The findings suggest that supportive classroom environments and interactive instructional practices play a crucial role in reducing students’ psychological burden. Accordingly, English language teachers are encouraged to integrate psychologically responsive and interactive teaching strategies to foster emotional safety and learner engagement, particularly within exam-oriented educational settings.